Proper use and impact of ‘Computer Assisted Semen Analysis’ technique on semen evaluation of farm animals - MICHOS (H.Α. ΜΙΧΟΣ) I. A.; BASIOURA (Α.Γ. ΜΠΑΣΙΟΥΡΑ) A. G.; BOSCOS (Κ.M. ΜΠΟΣΚΟΣ) C. M.; TSAKMAKIDIS (Ι.Α. ΤΣΑΚΜΑΚΙΔΗΣ) I. A. (Journal of the Hellenic Veterinary Medical Society, 2017)
Objective of this review is to present the use of ‘Computer Assisted Semen Analysis’ technique application in farm animal health management, in particular the steps for accurate semen evaluation and the impact of the method in predicting male animal fertility under field conditions. Requirements for proper use of the equipment, factors affecting the evaluation process and the role of the estimated parametres for fertility under field conditions are described. Special reference is made in sperm motility evaluation. It is concluded that the method is an effective and efficient tool for semen evaluation, provided good practices are strictly applied and adhered to, by means of which valid results may be obtained.